A new double tent maps for satellite image encryption - R.Khekan, Ahlam (International Journal of Engineering & Technology, 2018)
This paper introduces a simple and effective chaotic system using a combination of two existing one-dimension (1D) Chaotic maps (seed maps). Simulations and performance evaluations show that the proposed system can produce Many 1D chaotic maps with larger chaotic ranges and better chaotic behaviors compared to their seed maps. To Investigate its applications in multimedia security; a novel image encryption algorithm is proposed using the same set of Security keys; this algorithm can generate a completely different encrypted image each time when it is applied to the same original image. Experiments and security analysis demonstrate the algorithm’s excellent performance in image Encryption and various attacks. In conclusion, the proposed scheme is efficient in terms of sensitivity to the key, sensitivity to the ciphertext, good confusion, and diffusion. There is no possibility of an attacker breaking the cipher, as the scheme showed perfect confusion and diffusion properties, and can withstand known/chosen plaintext attacks.